Interplay of microplastics and bioturbation on atrazine dynamics in aquaculture sediments - Bokang Liu; Yifan Jiang; Rongrong Zhang; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2026)

Progressive failure mechanisms and stability assessment of geotextile bag tailings dams using upper-bound analysis - Zeming Wu; Xiaowen Liu; Jinhui Fan; Fuyong He (Geotextiles and Geomembranes, 2026)

Functional differences between healthy and stressed soils: Rare and abundant root exudates as a regulatory switch for quorum sensing in rhizosphere microbiota - Yueyi Liu; Zhenchao Wu; Zeming Ye; Liangyang Mao; Xiujun Tu; Yuhao Guo; Weige Yao; Ying Yang; Shuo Li; Jie Kang; Baiyan Cai; Jingping Ge (Plant and Soil, 2026)

Linearized dynamic modeling and pose prediction of AUV based on an improved EDMD framework - Qianqi Liu; Kuo Chen; Zhier Chen; Kai Ren; Zeming Wu; Jiancheng Yu (Ocean Engineering, 2026)

Non-additive effects of microplastics, atrazine, and sulfamethoxazole co-exposure on Penaeus vannamei health and environmental risks - Yinan Wang; Qiangqiang Shi; Weijia Gan; Feng Xu; Hao Liu; Liuquan Zhang; Rongrong Zhang; Jiong Chen; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2026)

Battling PFAS: Microbial frontlines and removal mechanisms in constructed wetlands - Yaoxuan Cheng; Jiacheng Shang; Xuanrui Liu; Zeming Shi; Xinyue Zhao; Lixin Li (Journal of Environmental Chemical Engineering, 2026)

Endoplasmic reticulum stress mediates oxidative stress-driven endothelial impairment and atherogenesis induced by sodium perfluorononenoxybenzene sulfonate exposure - Boxiang Zhang; Zeming Liu; Qing Li; Mingming Tian; Yue Gao; Hiroko Kishi; Dan Xu (Environmental Research, 2026)

Customizable sub-nanometer vertical-step grayscale lithography - Haonan Ma; Shijie Zhao; Xia Liu; Ziying Hu; Xu Han; Hongtao Li; Zeming Jin; Mingdi Zhang; Jixiang Li; Wenke Fu; Yunyun Dai; Yuan Huang; et al. (Science Bulletin, 2026)

Enhanced long-term oxidative remediation of calcium sulfate encapsulated KMnO4 for phenol-contaminated soil - Jia Shen; Yaxian Hu; Zeming Xie; Zili Jiang; Doaa M. Mustafa; Yang Liu; Yue Han; Xiuxiu Ruan (Journal of Hazardous Materials, 2026)

Fouling in beer clarification using polyethersulfone hollow fiber membranes - Hui Ye; Zeming Yan; Leiming Lou; Jie Sun; Junhui Zhong; Lei Zhang; Peng Liu; Zhonghou Feng (Journal of Food Engineering, 2026)

Cohydrothermal carbonization of cellulose and organic matter from municipal sewage sludge for the controllable synthesis of N-doped porous carbon for supercapacitor electrodes - Linxin Yin; Chang Liu; Yulu Yang; Zihan Du; Guanzhong Mu; Zeming Zhao; Changqing Cao; Pei-Gao Duan; Krzysztof Kapusta (Journal of Environmental Management, 2026)

Corrigendum to “Microstructure characteristics and corrosion behaviors of Mg alloys under various multiple-passes hot-rolling deformation” [Chem. Eng. J. 524 (2025) 169715] - Yuan Zhang; Zeming Li; Wei Liu; Yun Liu; Liansheng Chen (Chemical Engineering Journal, 2026)

Non-directly bonded single-atom pairs towards H2/CO electrooxidation - Tongtong Yang; Heng Liu; Hengjie Liu; Weiyi Zhao; Jiawei Ge; Wenhui Wang; Shuai Yang; Meijian Tang; Kai Wei; Kangcheng Wang; Zeming Qi; Xian Wang; et al. (Science Bulletin, 2026)

Geochemical signature and genesis of heavy metals in soils and sediments from a typical pyrite mining area in Southwestern China - Kai Zhao; Zeming Shi; Yinghai Zhu; Yixin Li; Qi Liu; Qiuyu Huang; Xiaohan Liu (Environmental Geochemistry and Health, 2026)

Engineering shape memory paper with superior strength, thermal stability, and recyclability through polyimide sizing - Qiang Wang; Zeming Zhang; Zihao Wang; Dehai Yu; Hui Gao; Shanshan Liu; Xingxiang Ji; Zhanhui Yuan (Chemical Engineering Journal, 2025)

Contrasting Behavior for Li-Mg Isotopes during Subduction: Insights from Garnet in the Yardoi Schists, Tibet - Xing Li; Yilin Xiao; Olivier Nadeau; Dong-Yong Li; Haiyang Liu; Zeming Zhang; Zhenhui Hou (Journal of Earth Science, 2025)

Using degrading endophytic bacteria to detoxify the phthalic acid esters in crops from contaminated soil - Xiangyu Liu; Xiangrui Du; Xiangzhi Zuo; Zeming Wang; Bozena Czech; Patryk Oleszczuk; Yanzheng Gao (Journal of Environmental Sciences, 2025)

Microstructure characteristics and corrosion behaviors of Mg alloys under various multiple-passes hot-rolling deformation - Yuan Zhang; Zeming Li; Wei Liu; Yun Liu; Liansheng Chen (Chemical Engineering Journal, 2025)

Extremely high toxicity of gaseous intermediate/semi volatile organic compounds emitted from typical incomplete biomass burning in China - Yueqian Wang; Di Wu; Zihua Guo; Xiu Chen; Yang Li; Yifei Tan; Zeming Ye; Yuzhe Liu; Yaoqiang Huo; Qing Li; Jianmin Chen (Journal of Hazardous Materials, 2025)

Controlled-release oxidants for in situ remediation of organic contaminated soil and groundwater: Material preparation, mechanisms, and applications - Jia Shen; Zili Jiang; Hongyun Shao; Zeming Xie; Yue Han; Jia Liu; Hongxin Chen; Shijin Feng; Yang Liu; Xiuxiu Ruan (Journal of Hazardous Materials, 2025)

Critical control points in Penaeus vannamei aquaculture: Dynamic tracking and comprehensive risk assessment of antibiotics - Feng Xu; Chenxue Yang; Hua Liu; Hao Liu; Mingze Chen; Yinliang Wu; Xizhi Shi; Zeming Zhang; Rongrong Zhang (Journal of Hazardous Materials, 2025)

Identification of Mitochondrial and Succinylation Modification-Related Gene Signature in Ischemic Stroke - Lixia Wang; Jishuai Zhao; Hui Cai; Xiaoling Ying; Yonglei Liu; Zeming Luo; Heyan Chen; Lin Yang (Molecular Neurobiology, 2025)

Co-exposure to enrofloxacin and atrazine enhances the hepatotoxicity in Larimichthys crocea by targeting the hypothalamic–pituitary–thyroid and gut–liver axes - Yinan Wang; Chenxue Yang; Qiangqiang Shi; Liuquan Zhang; Hao Liu; Jinjie You; Rongrong Zhang; Aili Sun; Suquan Song; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2025)

Seasonal and spatial variations of nutrients and environmental effects under anthropogenic influence in Daya Bay, China - Jincheng Zhao; Jiawei He; Cai Li; Zeming Yang; Cong Liu; Xianqing Zhang; Min Qin; Dejing Tang; Wen Zhou; Zhantang Xu; Yuanyue Cheng (Frontiers in Marine Science, 2025)
Nutrients are crucial factors for the growth of phytoplankton, and their biogeochemical processes directly impact marine biodiversity. In this study, based on two cruise observations in spring and summer of 2024, the seasonal and spatial variations of nutrients, chlorophyll a, and other ecological indicators in Daya Bay were explored. The results indicated that the average concentrations of dissolved inorganic nitrogen and silicate were 3.61 ± 3.99 µM and 26.27 ± 13.91 µM in summer, respectively, compared with 2.48 ± 1.53 µM and 23.8 ± 6.77 µM in spring. The average concentration of dissolved inorganic phosphate was 0.29 ± 0.12 µM in summer, lower than 0.32 ± 0.09 µM in spring. The stoichiometric proportion among nutrients at most monitoring stations were far from Redfield ratio, and a succession from N-limited to P-limited was observed. A transformation has been observed in the dominant composition of dissolved inorganic nitrogen, shifting from ammonia to total oxidized nitrogen as the main component, which is mainly attributable to the decrease in aquaculture activities in Daya Bay over the last 3 years. In addition, the warm wastewater discharge from nuclear power stations directly influences the distribution of phytoplankton in the surrounding areas. This study provides timely information regarding recent shifts in ecological indicators and is significant to the ecological protection, environmental management, and policy adjustment in Daya Bay.

Single-cell atlas profiling revealed cellular characteristics and dynamic changes after PD-1 blockade therapy of brain metastases from laryngeal squamous cell carcinoma - Yunzhi Zou; Hao Duan; Zekun Deng; Rong Xiang; Jixiang Zhao; Zhenhua Zhang; Wanming Hu; Yuanzhong Yang; Zeming Yan; Shujuan Wen; Zexian Liu; Gao Zhang; et al. (Molecular and Cellular Biochemistry, 2025)
Brain metastasis (BM) in laryngeal squamous cell carcinoma (LSCC) is uncommon but prognosis is poor. Anti-PD-1 immunotherapy benefits some advanced LSCC cases, yet its efficiency is limited by tumor complexity. We analyzed paired metastatic tumor samples from before and after immunotherapy using single-cell RNA sequencing (scRNA-seq), along with a primary LSCC dataset and bulk RNA sequencing. This identified changes post-immunotherapy and revealed differences in single-cell transcriptomes among LSCC, primBM, and neoBM. Our findings show that anti-PD-1 treatment suppresses metastasis-promoting pathways like VEGF and EMT in cancer cells, and alters immune cell functions. Notably, it upregulates T cell activation, leading to CD8 T cell exhaustion from excess heat shock proteins, notably HSPA8. However, CD8 T cell cytotoxic functions improve post-treatment. In myeloid cells, anti-PD-1 therapy enhances antigen presentation and promotes a proinflammatory shift post-metastasis. Additionally, NUPR1 is linked to BM in LSCC, and NEAT1 is a potential metastatic cancer cell cycle participant. Our study provides insights into cancer heterogeneity and the impact of PD-1 immunotherapy on metastasis, aiding precise diagnosis and prognosis.

Analysis of potential human accumulation differences and mechanisms of environmental new flame retardants: Based on in vitro experiments and theoretical calculations - Junchao Ma; Chao Qin; Juan Yan; Chunyu Wang; Yu Liu; Zeming Wang; Zekai Li; Yanzheng Gao (Science of The Total Environment, 2025)

The Role of MicroRNA-206 in the Regulation of Diabetic Wound Healing via Hypoxia-Inducible Factor 1-Alpha - Zeming Bai; Dapeng Zhou; Kai Tao; Feng Lin; Hongyi Wang; Haiwei Sun; Ruidi Liu; Zhe Li (Biochemical Genetics, 2025)
Successful wound healing in diabetic patients is hindered by dysregulated miRNA expression. This study aimed to investigate the abnormal expression of miRNAs in diabetic wound healing and the potential therapeutic role of modulating the miR-206/HIF-1α pathway. MicroRNA assays were used to identify differentially expressed miRNAs in diabetic wound sites and adjacent areas. In vitro models and a rat diabetic model were established to evaluate the effects of miR-206 on HIF-1α regulation and wound healing. The study revealed differential expression of miR-206 in diabetic wound tissues, its interaction with HIF-1α, and the inhibitory effect of miR-206 on cell growth under high glucose conditions. Modulating the miR-206/HIF-1α pathway using miR-206 antagomir promoted HIF-1α, CD34, and VEGF expression, ultimately enhancing diabetic wound healing.

Evaluating and enhancing the applicability of thermal comfort indices in diverse outdoor environments using Bayesian and random forest regression - Wenqiang Jing; Jiayan Liu; Zeming Qin; Teng Mu; Zhemin Ge; Yuting Dong (Energy and Buildings, 2024)

Insights into oral lentinan immunomodulation: Dectin-1-mediated lymphatic transport from Peyer's patch M cells to mononuclear phagocytes - Kaiping Wang; Yuxuan Liu; Zeming Zhang; Ziming Zheng; Wenqi Tang; Wangtianzi Teng; Xu Mu; Jinglin Wang; Yu Zhang (Carbohydrate Polymers, 2024)

Hydrophobic carbon quantum dots with Lewis-Basic nitrogen sites for electrocatalyst CO2 reduction to CH4 - Shuai Fu; Bijun Tang; Zeming Wang; Guangbin An; Mingwan Zhang; Kang Wang; Wenhui Liu; Huazhang Guo; Baohua Zhang; Liang Wang (Chemical Engineering Journal, 2024)

A microfluidic analyzer based on liquid waveguide capillary cells for the high-sensitivity determination of phosphate in seawater and its applications - Jincheng Zhao; Zeming Yang; Dejing Tang; Min Qin; Wen Zhou; Cong Liu; Zhantang Xu; Yuanyue Cheng; Xianqing Zhang; Cai Li (Analytica Chimica Acta, 2024)

Corrigendum to “Platelet membrane fusion liposome loaded with type I AIE photosensitizer to induce chemoresistance cancer pyroptosis and immunogenic cell death for enhancing cancer immunotherapy” [Chem. Eng. J. 476 (2023) 146276] - Hao Chen; Xi Luo; Qinghua Huang; Zeming Liu; Meng Lyu; Dexin Chen; Jianlan Mo; Daoming Zhu (Chemical Engineering Journal, 2024)

Unveiling the hidden risks: Pesticide residues in aquaculture systems - Weijia Gan; Rongrong Zhang; Zhi Cao; Hao Liu; Wentao Fan; Aili Sun; Suquan Song; Zeming Zhang; Xizhi Shi (Science of The Total Environment, 2024)

Endowing polymeric carbon nitride photocatalyst with CO2 activation sites by anchoring atomic cobalt cluster - Yaru Shang; Yijie Hou; Xun Cao; Hengjie Liu; Xiaoli Jin; Jiawei Liu; Chunshuang Yan; Yumin Qian; Li Song; Zeming Qi; Pin Song; Yansong Zhou; et al. (Chemical Engineering Journal, 2024)

Comparative antioxidant and metabolomic analysis for the identification of differential response of mussel (Mytilus coruscus) to four succinate dehydrogenase inhibitor fungicides - Ningbo Wang; Zeming Zhang; Yinan Wang; Liuquan Zhang; Aili Sun; Hua Liu; Xizhi Shi (Environmental Science and Pollution Research, 2024)

Improvement of rat hepatocellular carcinoma model induced by diethylnitrosamine - Runzhui Lin; Sitian Xie; Fengjie Xu; Zeming Chen; Jianrui Liu; Xingmu Liu (Tissue and Cell, 2024)

Synergistic benefits of Funneliformis mosseae and Bacillus paramycoides: Enhancing soil health and soybean tolerance to root rot disease - Zhichao Yang; Jie Kang; Zeming Ye; Wei Qiu; Jiaxin Liu; Xinbo Cao; Jingping Ge; Wenxiang Ping (Environmental Research, 2023)

Dietary oregano essential oil supplementation alters meat quality, oxidative stability, and fatty acid profiles of beef cattle - Pengjia He; Yu Lei; Ke Zhang; Rui Zhang; Yunpeng Bai; Zeming Li; Li Jia; Jinping Shi; Qiang Cheng; Yannan Ma; Xiaoqiang Zhang; Lishan Liu; et al. (Meat Science, 2023)

Platelet membrane fusion liposome loaded with type I AIE photosensitizer to induce chemoresistance cancer pyroptosis and immunogenic cell death for enhancing cancer immunotherapy - Hao Chen; Xi Luo; Qinghua Huang; Zeming Liu; Meng Lyu; Dexin Chen; Jianlan Mo; Daoming Zhu (Chemical Engineering Journal, 2023)

Suppressing hydrogen evolution and eliminating sulfation in lead-carbon batteries via potential-matching g-C3N4@rGO nanosheets - Daiwen Tao; Xiong Liu; Simiao Huang; Zeming Li; Hui Yang; Jinyu Wang; Qilong Zhang (Chemical Engineering Journal, 2023)

Toxic effects of three perfluorinated or polyfluorinated compounds (PFCs) on two strains of freshwater algae: Implications for ecological risk assessments - Liangliang Zhang; Xiaowei Zheng; Xianglin Liu; Jue Li; Yanyao Li; Zeming Wang; Nan Zheng; Xiangrong Wang; Zhengqiu Fan (Journal of Environmental Sciences, 2023)

Simultaneous determination and dietary intake risk assessment of 60 herbicide residues in aquatic products - Xinru Yu; Feng Xu; Rongrong Zhang; Hua Liu; Aili Sun; Liuquan Zhang; Zeming Zhang; Xizhi Shi (Science of The Total Environment, 2023)

Outdoor clothing choice for different populations in cold regions: A clothing choice prediction model based on machine learning - Wenqiang Jing; Yingdi Yin; Wei Luo; Jin Zhang; Zeming Qin; Xinyi Liu; Meng Zhen (Energy and Buildings, 2023)

Environmental profile, potential sources, and ecological risk of polycyclic aromatic hydrocarbons in a typical coastal bay and outer bay area - Yuyao Wu; Zeming Zhang; Wei Huang; Hua Liu; Rongrong Zhang; Haifeng Jiao; Aili Sun; Jiong Chen; Xizhi Shi (Environmental Science and Pollution Research, 2023)

Lead single atoms anchored on reduced graphene oxide as multifunctional additive for lead–carbon battery - Daiwen Tao; Xiong Liu; Zeming Li; Hui Yang; Jinyu Wang; Qilong Zhang (Chemical Engineering Journal, 2023)

Acute effects of three surface-modified nanoplastics against Microcystis aeruginosa: Growth, microcystin production, and mechanisms - Xiaowei Zheng; Liangliang Zhang; Chao Jiang; Jue Li; Yanyao Li; Xianglin Liu; Chengwei Li; Zeming Wang; Nan Zheng; Zhengqiu Fan (Science of The Total Environment, 2023)

Relative reinforcing effects of dibutylone, ethylone, and N-ethylpentylone: self-administration and behavioral economics analysis in rats - Miaojun Lai; Dan Fu; Zeming Xu; Han Du; Huifen Liu; Youmei Wang; Peng Xu; Wenhua Zhou (Psychopharmacology, 2022)

Intravenous immunoglobulin is effective in alleviating hepatic ischemia–reperfusion injury: a rat model study - Zeming Chen; Runzhui Lin; Hua Zhuo; Fengjie Xu; Xingmu Liu (Molecular Biology Reports, 2022)

Ammonium Impacts on Vibrations of Hydroxyl and Lattice of Phengite at High Temperature and High Pressure - Weihua Huang; Yan Yang; Zeming Qi; Wendi Liu; Zhongping Wang; Yan Liu; Qunke Xia (Journal of Earth Science, 2021)

Space target detection in optical image sequences for wide-field surveillance - Dan Liu; Xiaodong Wang; Yunhui Li; Zeming Xu; Jianing Wang; Zhonghui Mao (International Journal of Remote Sensing, 2020)

Crystal structure of impurity-free rhodochrosite (MnCO3) and thermal expansion properties - Wen Liang; Lin Li; Rui Li; Yuan Yin; Zeming Li; Xiqiang Liu; Shuangmin Shan; Yu He; Yong Meng; Zengsheng Li; Heping Li (Physics and Chemistry of Minerals, 2020)

Crystal structure of norsethite-type BaMn(CO3)2 and its pressure-induced transition investigated by Raman spectroscopy - Wen Liang; Lin Li; Yuan Yin; Rui Li; Zeming Li; Xiqiang Liu; Chaoshuai Zhao; Shuguang Yang; Yong Meng; Zengsheng Li; Yu He; Heping Li (Physics and Chemistry of Minerals, 2019)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

Correlation Between Iodine Intake and Thyroid Disorders: A Cross-Sectional Study from the South of China - Hengqiang Zhao; Yuan Tian; Zeming Liu; Xiaoyu Li; Mengyu Feng; Tao Huang (Biological Trace Element Research, 2014)

UHP metamorphic rocks from the Chinese continental scientific drilling project: I. Petrology and geochemistry of the main hole (0–2,050 m) - Zeming Zhang; Yilin Xiao; Zhiqin Xu; Jochen Hoefs; Jinsui Yang; Fulai Liu; J. G. Liou; Klaus Simon (Contributions to Mineralogy and Petrology, 2013)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Ultrahigh‐pressure metamorphic records hidden in zircons from amphibolites in Sulu Terrane, eastern China - Fulai Liu; Zeming Zhang; Ikuo Katayama; Zhiqin Xu; Shigenori Maruyama (Island Arc, 2003)
The amphibolites occur sporadically as thin layers and blocks throughout the Sulu Terrane, eastern China. All analyzed amphibolite from outcrop and drill cores from prepilot drill hole CCSD‐PP1 and CCSD‐PP2, Chinese Continental Scientific Drilling Project in the Sulu Terrane, are retrograded eclogites overprinted by amphibolite‐facies retrograde metamorphism, with characteristic mineral assemblages of amphibole + plagioclase + epidote ± quartz ± biotite ± ilmenite ± titanite. However, coesite and coesite‐bearing ultrahigh‐pressure (UHP) mineral assemblages are identified by Raman spectroscopy and electron microprobe analysis as inclusions in zircons separated from these amphibolites. In general, coesite and other UHP mineral inclusions are preserved in the cores and mantles of zircons, whereas quartz inclusions occur in the rims of the same zircons. The UHP mineral assemblages consist mainly of coesite + garnet + omphacite + rutile, coesite + garnet + omphacite, coesite + garnet + omphacite + phengite + rutile + apatite, coesite + omphacite + rutile and coesite + magnesite. Compositions of analyzed mineral inclusions are very similar to those of matrix minerals from Sulu eclogites. These UHP mineral inclusion assemblages yield temperatures of 631–780°C and pressures of ≥2.8 × 10 3 MPa, representing the P–T conditions of peak metamorphism of these rocks, which are consistent with those (T = 642–726°C; P ≥ 2.8 × 10 3 MPa) deduced from adjacent eclogites. These data indicate that the amphibolites are the retrogressive products of UHP eclogites.